The role of Mn-dependent peroxidase in dye decolorization by static and agitated cultures of Irpex lacteus - Svobodová, K; Erbanová, P; Sklenár, J; Novotný, C (Folia microbiologica, 2006)
Dye decolorization capacity of two white-rot fungi, Irpex lacteus and Phanerochaete chrysosporium, was compared in N-limited liquid cultures. The agitated cultures showed lower ability to decolorize azo dyes Reactive Orange 16 and Naphthol Blue Black than static cultures. Similar effect was also observed with other structurally different synthetic dyes. The effect of surfactants on the decolorization process is discussed. A significant increase in the Reactive Orange 16 decolorization by the agitated I. lacteus cultures was observed after adding 0.1% Tween 80, following a higher Mn-dependent peroxidase production. The in vitro dye decolorization using the purified enzyme proved its decolorization ability.
Keywords: Basidiomycota; Coloring Agents; Polysorbates; azosloučeniny; Azo Compounds; Peroxidases; Enzyme Induction; peroxidasy; enzymová indukce; barvicí látky; Phanerochaete; polysorbáty